2009
DOI: 10.1200/jco.2009.27.15_suppl.e15550
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant sunitinib following chemoradiotherapy (CRT) and surgery for esophageal cancer: A phase II trial

Abstract: e15550 Background: Locally advanced esophageal cancer (LAEC) has a 5-year survival of < 30 %. Most patients (pts) fail after curative intent tri-modality treatment with distant metastatic disease. This phase II trial aims to determine if adjuvant targeted therapy, after neoadjuvant CRT plus surgery for resectable LAEC, may impact on systemic disease without significant toxicity. Methods: Pts with LAEC of the thoracic esophagus or gastroesophageal junction, ECOG PS 0,1 and surgical candidates treated with: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Sunitinib is an oral multi-kinase inhibitor that targets VEGFR, platelet-derived growth factor receptor (PDGFR), and others. A phase II trial showed no therapeutic benefit of postoperative adjuvant therapy with sunitinib in combination with chemoradiotherapy in patients with locally advanced EC [36]. Another phase II trial found a trend toward improved OS with sunitinib in combination with FOLFIRII (irinotecan, 5-fluorouracil , and folic acid) in patients with advanced refractory esophageal cancer [37].…”
Section: Vegf/vegfr Targeted Drugs That Mainly Act On Esccmentioning
confidence: 99%
“…Sunitinib is an oral multi-kinase inhibitor that targets VEGFR, platelet-derived growth factor receptor (PDGFR), and others. A phase II trial showed no therapeutic benefit of postoperative adjuvant therapy with sunitinib in combination with chemoradiotherapy in patients with locally advanced EC [36]. Another phase II trial found a trend toward improved OS with sunitinib in combination with FOLFIRII (irinotecan, 5-fluorouracil , and folic acid) in patients with advanced refractory esophageal cancer [37].…”
Section: Vegf/vegfr Targeted Drugs That Mainly Act On Esccmentioning
confidence: 99%
“…Abstract reports in the metastatic and adjuvant settings are available. The University Health Network of Toronto has reported early feasibility data from a phase II trial (abstract form) on adjuvant sunitinib in surgically resected stage II or III esophageal cancer patients after neo-adjuvant cisplatin/ irinotecan [Horgan et al 2009]. A phase II trial has been reported (abstract form) on the combination of sorafenib and docetaxel/cisplatin in metastatic or advanced gastric/GEJ cancer.…”
Section: Anti-vegf Therapymentioning
confidence: 99%